2014
DOI: 10.1097/coh.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centered care for people living with multimorbidity

Abstract: Purpose of review The purpose of this review is to consider a patient-centred approach to the care of people living with HIV (PLWH) who have multimorbidity, irrespective of the specific conditions. Recent findings Interdisciplinary care to achieve patient-centred care for people with multimorbidity is recognized as important, but the evaluation of models designed to achieve this goal are needed. Key elements of such approaches include patient preferences, interpretation of the evidence, prognosis as a tool t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…19,40 Sixteen percent of HIV patients in Ontario receive care exclusively from family physicians with lower HIV experience; our results suggest potential disparities in ART among these patients. Because we also found that this influence of family physician HIV experience is mitigated by having an HIV specialist within their model of care, in order to ensure adequate ART prescribing, care delivery models for people with HIV should include either an HIV specialist or a family physician with considerable HIV experience.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…19,40 Sixteen percent of HIV patients in Ontario receive care exclusively from family physicians with lower HIV experience; our results suggest potential disparities in ART among these patients. Because we also found that this influence of family physician HIV experience is mitigated by having an HIV specialist within their model of care, in order to ensure adequate ART prescribing, care delivery models for people with HIV should include either an HIV specialist or a family physician with considerable HIV experience.…”
Section: Discussionmentioning
confidence: 80%
“…We recommend that such access to HIV expertise, whether through direct contact with HIV specialists or through strategies that give decision support to family physicians, be provided within a collaborative model that allows patients to retain continuity with their family physicians to ensure a comprehensive approach to care delivery. 19,[40][41][42] …”
Section: Discussionmentioning
confidence: 99%
“…Whether investments in this line of research will lead to important biologic insights and improved clinical management remains uncertain. There are tantalizing clues about overlapping roles of chronic viral infection, hypercoagulability, inflammation, immune dysregulation and senescence 5, 6, 34, 35 as well as the critical importance of more integrative scientific thinking across diseases, medical and research disciplines, and ages 22, 36, 37 . Outside HIV research, there is a growing appreciation for the importance of other chronic viral infections including hepatitis C and cytomegalovirus.…”
mentioning
confidence: 99%
“…Others are focused on more integrated issues of aging including metabolism 15 , multimorbidity 21 , geriatric syndromes 35 , frailty 36 , and functional status 28 . Still others focus on systems and approaches to care 37 . Finally, we begin the collection with an updated description of the demographics of aging with HIV 2 and end with a cautionary paper on how to identify appropriate uninfected comparators 26 and an article focused on pressing research questions 5 .…”
mentioning
confidence: 99%
“…Leading researchers, along with other key stakeholders including the PHCAG and the RACGP, argue the complexities of providing multimorbidity care requires a focus on patient-centred care that emphasises patients' priorities and preferences for care (13,25,54,59,(126)(127)(128)(129). Patient-centred care is a philosophy of care that has long been a cornerstone of family medicine but is difficult both to operationalise and measure (125).…”
Section: Practice Levelmentioning
confidence: 99%